Multicenter, Prospective, Controlled, Before-and-After, Quality Improvement Study (Stroke123) of Acute Stroke Care. Issue 6 (June 2019) - Cadilhac, Dominique A.; Grimley, Rohan; Kilkenny, Monique F.; Andrew, Nadine E.; Lannin, Natasha A.; Hill, Kelvin; Grabsch, Brenda; Levi, Christopher R.; Thrift, Amanda G.; Faux, Steven G.; Wakefield, John; Cadigan, Greg; et al.
Abstract : Background and Purpose—: Hospital uptake of evidence-based stroke care is variable. We aimed to determine the impact of a multicomponent program involving financial incentives and quality improvement interventions, on stroke care processes. Methods—: A prospective study of interventions to improve clinical care quality indicators at 19 hospitals in Queensland, Australia, during 2010 to 2015, compared with historical controls and 23 other Australian hospitals. After baseline routine audit and feedback (control phase, 30 months), interventions involving financial incentives (21 months) and then addition of externally facilitated quality improvement workshops with action plan development (9 months) were implemented. Postintervention phase was 13 months. Data were obtained for the analysis from a previous continuous audit in Queensland and subsequently the Australian Stroke Clinical Registry. Primary outcome: change in median composite score for adherence to ⩽8 indicators. Secondary outcomes: change in adherence to self-selected indicators addressed in action plans and 4 national indicators compared with other Australian hospitals. Multivariable analyses with adjustment for clustered data. Results—: There were 17 502 patients from the intervention sites (median age, 74 years; 46% women) and 20 484 patients from other Australian hospitals. Patient characteristics were similar between groups. There was an 18% improvement in the primary outcome across the study periods (95% CI, 12%–24%). The largest improvement was following introduction of financial incentives (14%; 95% CI, 8%–20%), while indicators addressed in action plans provided an 8% improvement (95% CI, 1%–17%). The national score (4 indicators) improved by 17% (95% CI, 13%–20%) versus 0% change in other Australian hospitals (95% CI, −0.03 to 0.03). Access to stroke units improved more in Queensland than in other Australian hospitals ( P <0.001). Conclusions—: The quality improvement interventions significantly improved clinical practice. The findings were primarily driven by financial incentives, but were also contributed to by the externally facilitated, quality improvement workshops. Assessment in other regions is warranted. Abstract : Supplemental Digital Content is available in the text.